Optimization of the vanes form of transsonic cascades of compressors of gas-turbine engines - Мазур, Александр Павлович; Куничник, Павел Иванович; Зюзьков, Владимир Николаевич; Роздобудько, Вадим Васильевич; Кулик, Константин Сергеевич (Eastern-European Journal of Enterprise Technologies, 2012)
Analysis of optimization algorithms namely Genetic Algorithm (GA) and algorithms of Simulated Annealing (SA) that are used in aerodynamic optimization of transonic compressor cascade. The aim of the research was to analyze the possibility of re-profile blades of a turbine engine